1994
DOI: 10.1038/nbt0994-915
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Bacillus thuringiensis Crystal Proteins with New Properties: Possibilities for Resistance Management

Abstract: To obtain Bacillus thuringiensis crystal proteins with new properties and to identify the regions involved in insecticidal activity, we generated hybrid genes composed of cryIC and cryIE by in vivo recombination. Analysis of the hybrid proteins showed that domain III of CryIC is involved in the toxicity towards Spodoptera exigua and Mamestra brassicae. Transfer of this domain to CryIE, which is not active against these insects, resulted in a new protein with a broader activity. This hybrid protein binds to dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
92
1
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(96 citation statements)
references
References 15 publications
1
92
1
2
Order By: Relevance
“…Alanine substitution of residues 541-544 of domain III of Cry1Ca in the hybrid G27 toxin abolished the activity of this hybrid against S. exigua, but not against M. sexta [16]. These results suggested an important role for domain III, as well as for domain II, in the mode of action of Cry1Ca, including insect specificity.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Alanine substitution of residues 541-544 of domain III of Cry1Ca in the hybrid G27 toxin abolished the activity of this hybrid against S. exigua, but not against M. sexta [16]. These results suggested an important role for domain III, as well as for domain II, in the mode of action of Cry1Ca, including insect specificity.…”
Section: Introductionmentioning
confidence: 62%
“…Wild-type Cry1Ca and mutant protoxins were expressed in Escherichia coli strain XL-1 Blue, extracted, solubilized and trypsin treated as described previously [16]. Briefly, each 1 g of cell culture expressing the different toxins was resuspended in 3 ml of lysis buffer (50 mM Tris/HCl, pH 8.0, 5 mM EDTA, 100 mM NaCl) by vigorous shaking, and then 800 µg of lysozyme was added per g of pellet.…”
Section: Mutagenesis and Protein Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…One strategy to delay resistance is to use alternative insecticidal proteins with different modes of action (Bosch et al 1994;Saraswathy and Kumar 2004). Researchers found that the resistance allele of P. xylostella confers cross-resistance to Cry1Aa, Cry1Ab, Cry1Ac, Cry1Fa and Cry1Ja, but not to Cry1Ba, Cry1Bb, Cry1Ca, Cry1Da, Cry1Ia or Cry2Aa (Tabashnik et al 1997(Tabashnik et al , 2000Heckel et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Cry proteins share a common three domain structure (Li et al 1991). In simple words, hybrid (Synthetic) toxins produced through inclusion of a domain from another toxin results in increased potency of the fused protein by the shift in receptor binding (Bosch et al 1994). In this direction, a chimeric Bt gene cry1AcF with cry1Ac (domain I & II) and cry1F (domain III) was developed to improve the insecticidal property of the toxin (Chakrabarti et al 1998).…”
Section: Introductionmentioning
confidence: 99%